2009
DOI: 10.1503/cmaj.090917
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Secondary Prevention in Coronary Artery Disease trial

Abstract: Background: Proven efficacious therapies are sometimes underused in patients with chronic cardiac conditions, resulting in suboptimal outcomes. We evaluated whether evidence summaries, which were either unsigned or signed by local opinion leaders, improved the quality of secondary prevention care delivered by primary care physicians of patients with coronary artery disease. Methods:We performed a randomized trial, clustered at the level of the primary care physician, with 3 study arms: control, unsigned statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Data are urgently needed to clarify how routinely incorporating information on eGFR into routine care could improve outcomes rather than simply increasing physician workload. Because the effect of treatment recommendations delivered at point of care may be increased by accompanying them with endorsements from respected local physicians (22,36), future use of automated reminders should consider incorporating opinion leaders as signatories or other enabling strategies such as patient activation mechanisms and the involvement of allied health professionals (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are urgently needed to clarify how routinely incorporating information on eGFR into routine care could improve outcomes rather than simply increasing physician workload. Because the effect of treatment recommendations delivered at point of care may be increased by accompanying them with endorsements from respected local physicians (22,36), future use of automated reminders should consider incorporating opinion leaders as signatories or other enabling strategies such as patient activation mechanisms and the involvement of allied health professionals (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, no prior studies have evaluated the effect of an enhanced managementbased eGFR prompt. Moreover, whether point-of-care reminders improve processes of care and clinical outcomes is uncertain (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion Although primary care physicians and specialists have made great inroads in the control of cardiovascular risk factors for patients with coronary disease over the past decade, 31 stroke prevention strategies need to extend beyond the current emphasis on antithrombotic agents and evaluation for carotid endarterectomy. We found that a nurse-led case management program based on monthly evaluation of risk factors, patient counselling and feedback to primary care physicians improved control of key risk factors for stroke (hypertension and dyslipidemia) by 6 months.…”
Section: 30mentioning
confidence: 99%
“…Another important caveat is that we will be using patient self-report for main outcome measurements—an approach which has previously been used in a similar trial [38]. We are planning to evaluate the validity of self-report data in our study by comparing patient reported medication use (including the MMAS) with data recorded in administrative databases for a subsample of participants above age 65 (for whom data are accessible using the Ontario Drug Database).…”
Section: Discussionmentioning
confidence: 99%
“…Three other trials have evaluated the role of reminder letters to the primary care provider (with or without patient reminders) to improve adherence to evidenced-based cardiovascular therapies: one in the USA, one in the UK, and one in Canada [36-38]. The American trial focused on beta-blocker use post-MI and found a small increase in compliance (proportion of days covered), with a number needed to treat of 16 for achieving high adherence, but no change in the proportion who discontinued their beta-blocker.…”
Section: Introductionmentioning
confidence: 99%